Reception Analysis to Female Reader in Indonesia about Sadomasochism on Fifty Shades of Grey Novels - Dhita Gracia Samosir; Dr. Hapsari Dwiningtyas, S.Sos, MA (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
This research is used to see differences interpretation on female reader group about sadomasochism on novel Fifty Shades of Grey. Text on the media, on this case on novel Fifty Shades of Grey offering the reader to understand sadomasochism as a sexual activity which can give sexual pleasure as a preferred reading, the dominant meaning from text’s novel then compared to interview result’s analysis towards female reader, specifically in Indonesia. The research is aim to look the social values construction that offered from novel Fifty Shades of Grey and the interpretation of female reader group about sexual acitivity like sadomasochism. The research using method Reception Analysis, and other theories, like first, Concept of Symbolic Control on Women Sexuality from Bourdieu and Foucault, Domestic Violence Theory and The Male Control Theory from a journal by Bauminster. The teories is used to see the interpretation of female reader group have on sadomasochism that offered on preferred reading by text on Fifty Shades of Grey. The results is showed the differences interpretation on each female reader group. The diversity is influenced by age, educational level, marriage status, up to background of knowledge on each one female reader had on them. There are female reader who accept the dominant meaning on text that they interprete sadomasochism as a sexual activity that could give pleasure. There’s also a group that negotiate the dominant meaning with their internal values and there’s also a group of female reader that declining the dominant meaning on text Fifty Shades of Grey, that sadomasochism is not a pleasure. The dominant group, is the female reader group that declining the offer and not accepting sadomasochism as a sexual pleasure.